Islamic Law Thought: The Concept of Wages for Workers According to Syafi’iyah Fiqh and Positive Law - T. Wildan (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2022)
This article aims to analyze the system of determining workers’ wages according to Syafi’iyah fiqh and positive law; the government is looking for an alternative approach to national labour issues, especially in the mechanism of applying wages that are by the efforts of workers as contained in the book of the Syafi’iyah school of thought. This research aims to determine the system for setting workers’ wages in Indonesia and to contribute ideas to Islamic economic law. At the same time, it can be applied in the life of Islamic society in the era of globalization and free markets. The method used in this paper is descriptive analysis with a normative juridical approach. The primary sources used in this writing are books by fiqh scholars from the Syafi’iyah school of thought and laws related to workers’ wages, namely Government Regulation (PP) Number 36 of 2021 concerning wages. The findings in this study are that workers’ salaries in Government Regulation (PP) Number 36 of 2021 obtained by workers are still different from the work performed by workers, and the risks they face are disproportionate. At the same time, the determination of wages, according to Syafi’iyah fiqh, must be based on the principles of justice that workers, employers, and the government feel. The focus of justice is translated as setting a minimum wage based on meeting the most basic needs of a worker. Thus, the most critical wage, according to Syafi’iyah fiqh, is real wages, not nominal wages (money).